The immature stages of Myiotabanus barrettoi fairchild (Tabanidae-Diptera-Insecta) - Coscarón, Sixto (1996)
Larva and pupa of Myiotabanus barrettoi living between leaves of Pistia stratiotes in ponds of Formosa Province (Argentina) are described. As immature stages of Lepiselaga crassipes inhabit the same environment and have very a similar appearance, new information on ornamentation and morphology is added to differentiate both species. Larvae and pupae were maintained individually in moist vials at laboratory temperature until adults emerged.